RACE: Real-time Applications over Cloud-Edge - Chandramouli, Badrish; Claessens, Joris; Nath, Suman; Santos, Ivo; Zhou, Wenchao (ACM SIGMOD International Conference on Management of Data (SIGMOD 2012), 2012)
The Cloud-Edge topology - where multiple smart edge devices such as phones are connected to one another via the Cloud - is becoming ubiquitous. We demonstrate RACE, a new framework and system for specifying and efficiently executing distributed real-time applications in the Cloud-Edge topology. RACE uses LINQ for StreamInsight to succinctly express a diverse suite of useful real-time applications. Further, it exploits the processing power of edge devices and the Cloud to partition and execute such queries in a distributed manner. RACE features a novel cost-based optimizer that efficiently finds the optimal placement, minimizing global communication cost while handling multi-level join queries and asymmetric network links.